New Polymer Syntheses Part 59. Synthesis and Characterization of New Polyamides and Copolyamides Containing Thianthrene Moiety and Based on Methyl- and/or Tertiarybutyl-Cyclohexanone in the Main Chain - Aly, Kamal I.; Kuckling, Dirk (Journal of Research Updates in Polymer Science, 2015)
Two new series of polyamides and copolyamides based on methyl-cyclohexanone and tertiary-butyl-cyclohexanone in the main chain were synthesized via the solution polymerization of 2,6-bis(m-aminobenzylidene)-methylcyclohex-anone VI, 2,6-bis(m-aminobenzylidene)tertiary-butyl-cyclohexanone VIII, and its copolyamides with p-phenylene diamines and m-phenylene diamines with diacid chlorides of thianthrene (2,7-Dichloroformylthianthrene-5,5`,10,10`-tetraoxide IV. These polyamides and copolymides ranged from yellow to orange color and had inherent viscosity up to 0.35-0.89 dL/g. All the polyamides and copolymides were insoluble in common organic solvents but dissolved completely in concentrated H2SO4. The thermal stabilities of the prepared polyamides were evaluated by TGA and DTG analyses. X– ray analysis showed these polymers having low degree of crystallinity in the region 2q = 5 – 60°. The morphological properties of some selected polyamides were detected by SEM.